TINJAUAN YURIDIS PENEGAKAN HUKUM DAN KEADILAN DALAM TINDAK PIDANA KORUPSI PASCA LAHIRNYA KUHP NASIONAL - Sandi Purnomo (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
This research is motivated by the enactment of the National Criminal Code (KUHP), which brought about a paradigm shift in the criminal law system in Indonesia, including in the enforcement of corruption laws. The research problem focuses on how law enforcement and the principle of justice are applied in corruption crimes after the enactment of the National Criminal Code, as well as the legal obstacles that arise in its implementation. The purpose of this research is to analyze the legal review of law enforcement against corruption crimes and examine the extent to which the value of justice is reflected in the application of law after the establishment of the National Criminal Code. This research uses a qualitative research method with a normative legal approach through the analysis of legislation, legal literature, and court decisions related to corruption crimes. The theories used in this research include the theory of law enforcement by Soerjono Soekanto, the theory of justice by John Rawls, and the theory of legal certainty to examine the relationship between law, justice, and the effectiveness of law enforcement. The results of the study show that the birth of the National Criminal Code provides updates in the criminal system and strengthens the principle of legality, but its implementation still faces various obstacles, such as overlapping regulations with special laws on corruption crimes, differences in interpretation by law enforcement officials, and the less than optimal application of the principle of substantive justice in the process of enforcing corruption laws in Indonesia